2016
DOI: 10.3389/fmicb.2016.01939
|View full text |Cite
|
Sign up to set email alerts
|

A Bioengineered Nisin Derivative, M21A, in Combination with Food Grade Additives Eradicates Biofilms of Listeria monocytogenes

Abstract: The burden of foodborne disease has large economic and social consequences worldwide. Despite strict regulations, a number of pathogens persist within the food environment, which is greatly contributed to by a build-up of resistance mechanisms and also through the formation of biofilms. Biofilms have been shown to be highly resistant to a number of antimicrobials and can be extremely difficult to remove once they are established. In parallel, the growing concern of consumers regarding the use of chemically der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…These results indicate that nisin was able to reduce the capacity of both strains to generate their biofilms, and that in combination with ethanol (4–6%) a nisin concentration of 6 μg/mL was able to prevent the formation of biofilms. These results are in agreement with recent studies that indicate that antimicrobial peptides, such as nisin, can act as biofilm disruptors due to their ability to permeabilize bacterial membranes ( Smith et al, 2016 ; Grassi et al, 2017 ). Nevertheless, when we performed the experiments of addition of the culture broth containing binary combinations of 6 μg/mL nisin and ethanol (0, 2, 4, 6, 8% v/v) on a previously formed biofilm, instead of on planktonic cells of O. oeni IS151 and L. mesenteroides J32, the results were completely different: in all cases the pre-formed biofilms enlarged after 24 h incubation with the culture broth containing the subinhibitory concentrations of both nisin and ethanol ( Figure 3 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results indicate that nisin was able to reduce the capacity of both strains to generate their biofilms, and that in combination with ethanol (4–6%) a nisin concentration of 6 μg/mL was able to prevent the formation of biofilms. These results are in agreement with recent studies that indicate that antimicrobial peptides, such as nisin, can act as biofilm disruptors due to their ability to permeabilize bacterial membranes ( Smith et al, 2016 ; Grassi et al, 2017 ). Nevertheless, when we performed the experiments of addition of the culture broth containing binary combinations of 6 μg/mL nisin and ethanol (0, 2, 4, 6, 8% v/v) on a previously formed biofilm, instead of on planktonic cells of O. oeni IS151 and L. mesenteroides J32, the results were completely different: in all cases the pre-formed biofilms enlarged after 24 h incubation with the culture broth containing the subinhibitory concentrations of both nisin and ethanol ( Figure 3 ).…”
Section: Resultssupporting
confidence: 93%
“…With respect to nisin, to our knowledge this is the first report on the activation of biofilm synthesis by a subinhibitory concentration of this bacteriocin. Previous studies reported the inhibitory effect of nisin on the growth and biofilm formation of pathogenic bacteria, such as Listeria ( Smith et al, 2016 ), Staphylococcus ( Dosler and Mataraci, 2013 ; Okuda et al, 2013 ; Field et al, 2016a ), Streptococcus ( Tong et al, 2014 ), Enterococcus ( Taneja et al, 2015 ), Bacillus and Salmonella ( Bag and Chattopadhyay, 2017 ), Bacillus and Clostridium spores ( Egan et al, 2016 ), Pseudomonas ( Field et al, 2016b ), and Escherichia coli ( Al Atya et al, 2016 ), but none of them reported any biofilm activating effect by subinhibitory concentrations. Regarding O. oeni , a biocide effect of nisin on O. oeni cells in biofilms formed on stainless steel surfaces was already reported ( Nel et al, 2002 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Organic acids are widely used for food preservation ( Young and Foegeding, 1993 ). The antimicrobial activity of nisin or other bacteriocins against L. monocytogenes F6854 can be enhanced in the presence of organic acids ( Smith et al, 2016 ). Overall, the antibacterial activity of L. lactis N8-r-lecCI supernatant can be further enhanced in the presence of the low concentration of EDTA.…”
Section: Discussionmentioning
confidence: 99%
“…Nisin A bioengineered derivative in combination with available food additives, such as cinnamaldehyde (35 mg ml À1 ) or citric acid (175 mg ml À1 ), can eradicate the L. monocytogenes biolm. 73 It can be concluded that food additives could enhance the antimicrobial treatment of biolms in the food industry. 4.1.2.…”
Section: Prevention Of Biolm Formationmentioning
confidence: 99%